한국 아동 및 청소년의 단백질 섭취와 과체중 및 비만과의 연관성: 2014–2019년 국민건강영양조사 자료를 활용하여 - 김수민(Sumin Kim); 하경호(Kyungho Ha) (Journal of nutrition and health, 2023)
Purpose: Proteins are major components of the body and essential nutrients for proper growth and development. However, studies on protein intake in children and adolescents are insufficient. A few previous studies have reported the relationship with growth indicators, but results vary depending on the source of protein. Therefore, the current study investigates the relationship between protein intake and overweight and obesity among children and adolescents in Korea. Methods: Based on the 2014-2019 Korea National Health and Nutrition Examination Survey, 5,567 children and adolescents aged 6-18 years, who participated in a 24-hour dietary recall with information on height and weight, were included in this study. Protein intake was estimated as percentage of total energy (% of energy) and was classified into animal and plant protein according to the food source. Overweight and obesity were defined using the 2017 pediatric and adolescent growth chart. Results: Total protein intake of the subjects was estimated as 14.5% of total energy (animal protein 8.3% and plant protein 6.3%). The group with the highest total protein intake had a higher odds ratio (OR) of overweight/obesity than those with the least protein intake (OR, 1.36, 95% confidence interval (CI), 1.10-1.67, p for trend = 0.003). When classified by food source, the group with the highest animal protein intake had a significantly higher OR of overweight/obesity than subjects with the lowest intake (OR, 1.30, 95% CI, 1.05-1.61, p for trend = 0.016). However, plant protein was not significantly associated with overweight/obesity. Conclusions: These findings suggest that a high intake of animal protein in children and adolescents increases the risk of being overweight and obese. In order to develop normal growth and prevent obesity in the future, it is necessary to determine an appropriate protein intake level through nutrition education programs and prospective studies on balanced protein intake. 본 연구는 2014년부터 2019년까지 국민건강영양조사 자료를 이용하여 아동·청소년의 단백질 섭취와 성장지표 및 비만과의 관련성을 규명하고자 하였다. 본 연구의 대상자는 6-18세 아동 및 청소년 5,567명으로 1일 24시간 회상법 자료를 이용하여 단백질 섭취량을 평가한 결과는 다음과 같다. 대상자의 평균 총 단백질 에너지섭취비율은 14.5 ± 0.1%로 청소년 및 남아에서, 교육수준 및 가구소득수준이 높을수록 높았다. 단백질 섭취량을 삼분위수로 분류했을 때, 총 단백질 섭취량이 가장 높은 그룹이 가장 적게 섭취한 그룹에 비해 과체중 및 비만의 교차비가 1.36배 높았다. 동물성 단백질은 과체중 및 비만과 양의 연관성이 있었으나, 식물성 단백질은 유의한 연관성이 없었다. 동물성 단백질을 가장 많이 섭취한 남아와 청소년에서 가장 적게 섭취한 그룹에 비해 과체중 및 비만의 교차비가 유의하게 높았으나 지방 섭취량을 보정 한 이후에는 유의성이 사라졌다. 총 단백질 섭취량이 증가하면 동물성 단백질 섭취는 증가하지만 식물성 단백질은 감소했으며, 탄수화물 섭취량은 감소하고 지방 섭취량은 증가하는 경향을 보였다. 특히, 동물성 단백질을 가장 많이 섭취하는 그룹의 육류 섭취횟수는 4.1회로 가장 적게 섭취하는 그룹 1.2회에 비해 약 4배 높았다. 이상과 같은 결과를 통해 최근 10년간 우리나라 아동 및 청소년의 총 단백질과 동물성 단백질 섭취량은 증가하였으며, 총 단백질 및 동물성 단백질의 높은 섭취는 과체중 및 비만의 위험 증가와 관련이 있었다. 유년시절의 비만은 당뇨병, 심혈관질환 등과 같은 만성질환의 위험을 높이고, 성인 비만으로도 이어질 가능성이 높다. 특히, 식생활은 아동비만에 주요한 영향을 미치므로 향후 아동 및 청소년의 성장발달과 비만예방을 위해 전향적 연구수행을 통한 단백질 적정섭취 가이드라인 및 효과적인 영양교육 프로그램 마련이 필요할 것이다.